2020
DOI: 10.1590/1980-57642020dn14-020011
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect assessment of functional abilities in patients with Parkinson’s disease transitioning to dementia

Abstract: ABSTRACT. Cognitive impairment is common in patients with Parkinson’s disease (PD), and evaluation of functional abilities is crucial for diagnosis of dementia. Objective: We evaluated differences between direct and indirect functional assessment methods to evaluate functional abilities in PD patients. Methods: We evaluated 32 patients with PD and suspected mild dementia using direct and indirect assessment methods. Results: There was a significant difference between the scores of direct and indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 29 publications
0
12
0
5
Order By: Relevance
“…Corroborando com esses dados, dois estudos brasileiros sugeriram que o questionário da pílula é menos sensível do que outros instrumentos para detectar comprometimento funcional 15,33 . Estudos prévios avaliando pacientes brasileiros com DDP utilizaram alguns instrumentos para avaliar habilidades funcionais, incluindo o questionário de atividades funcionais de Pfeffer, Avaliação de Incapacidade em Demência (DAD), Questionário de Informante sobre Declínio Cognitivo em Idosos (IQCODE), Pill Questionnaire, teste de telefone e Avaliação Direta da Capacidade Funcional (DAFA) 15,[33][34][35][36][37] . Dois estudos avaliaram a precisão do Pfeffer para detectar comprometimento funcional em pacientes com DP 33,37 .…”
Section: Caraterísticas Clínicas Principaisunclassified
“…Corroborando com esses dados, dois estudos brasileiros sugeriram que o questionário da pílula é menos sensível do que outros instrumentos para detectar comprometimento funcional 15,33 . Estudos prévios avaliando pacientes brasileiros com DDP utilizaram alguns instrumentos para avaliar habilidades funcionais, incluindo o questionário de atividades funcionais de Pfeffer, Avaliação de Incapacidade em Demência (DAD), Questionário de Informante sobre Declínio Cognitivo em Idosos (IQCODE), Pill Questionnaire, teste de telefone e Avaliação Direta da Capacidade Funcional (DAFA) 15,[33][34][35][36][37] . Dois estudos avaliaram a precisão do Pfeffer para detectar comprometimento funcional em pacientes com DP 33,37 .…”
Section: Caraterísticas Clínicas Principaisunclassified
“…Functional changes and homeostasis usually appear naturally due to the senescence physiology and impact on pharmacokinetics and pharmacodynamics, with the potential to influence the drug therapy safety and effectiveness. 1,2 One of the senility processes designs, characterized by a gradual and pathological decline in all body systems functioning, has determined the highest frequency of frailty and comorbidities and, by consequence, the polypharmacy in the older adults. The long-lived population is one of the largest consumers of drugs 3 and studies have shown that the use of inappropriate medications is prevalent in older adults patients, as well as adverse reactions and drug interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Functional changes and homeostasis usually appear naturally due to the senescence physiology and impact on pharmacokinetics and pharmacodynamics, with the potential to influence the drug therapy safety and effectiveness. 1 , 2…”
Section: Introductionmentioning
confidence: 99%
“…Assessment instruments by indirect observation based on the report of a caregiver are widely used 12 , considering that the lack of awareness of the deficit is a characteristic of the dementia condition 13 . Such instruments can bring information bias, underestimating or overestimating 14 the performance capacity of the person with dementia 12 . Although the combined use of instruments for direct and indirect observation of performance is recommended 13 , those available in our environment do not allow observation of the same items of routine tasks, making it difficult to compare perceptions and identify discrepancies between different sources.…”
Section: Introductionmentioning
confidence: 99%